Functional magnetic resonance imaging of category-specific cortical activation: evidence for semantic maps - Spitzer, Manfred; Kischka, Udo; Gückel, Friedemann; Bellemann, Matthias E.; Kammer, Thomas; Seyyedi, Soraya; Weisbrod, Matthias; Schwartz, Andreas; Brix, Gunnar (Brain research. Cognitive brain research, 1998)
Functional magnetic resonance imaging (fMRI) was used to examine the pattern of cortical activity during a picture naming task. Subjects (n=12) had to covertly name either animals or furniture items. Functional scanning was performed using a conventional 1.5-Tesla whole-body MRI system. Images obtained during naming the two categories were compared using a non-parametric test. The study revealed evidence for domain-specific lexical regions in left middle, right middle and inferior frontal areas, as well as in superior and middle temporal areas. The results corroborate neuropsychological data and demonstrate directly and non-invasively in human volunteers that semantic representations in frontal and temporal areas are, to some degree, localized and possibly implemented as multiple maps. A completely distributed storage of semantic information is rendered unlikely.
Gesehen am 25,091.2021